Paciente femenino de 4 años de edad con diagnóstico de rinitis alérgica. - Minaya Santana, Sixto Joel (2021)
Allergic rhinitis is a chronic inflammatory disease mainly of the nasal mucosa which presents symptoms such as itching, rinorrea, nasal congestion and sneezing. In Ecuador, it is expected that 15 and 28% of the population suffers from allergic rhinitis, showing a high rate of incidence of this pathology. Emphasizing that the largest percentage of the population with this disease is not treated in time with adequate treatment, which causes self-limitations in the lives of these patients. In this work, all the information regarding allergic rhinitis, its definition, epidemiology, clinical picture, non-pharmacological and pharmacological treatment is compiled. With the information in this work, it is estimated that it will serve as a guide and help for the different types of professionals in the health area, but especially respiratory therapists in the correct management of patients with this disease.